2022
DOI: 10.3389/fnins.2022.861480
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of High-Frequency Oscillations With Neuromorphic Spiking Neural Networks

Abstract: Interictal high-frequency oscillations (HFO) detected in electroencephalography recordings have been proposed as biomarkers of epileptogenesis, seizure propensity, disease severity, and treatment response. Automatic HFO detectors typically analyze the data offline using complex time-consuming algorithms, which limits their clinical application. Neuromorphic circuits offer the possibility of building compact and low-power processing systems that can analyze data on-line and in real time. In this review, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…The Spectrum detector was developed on UMCU intraoperative ECoG recordings 11 and then applied to the USZ intraoperative ECoG data 9 , 10 . The SW-SNN detector was then applied to the same dataset for the patients whose resection was guided by hd-ECoG 15 , 16 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Spectrum detector was developed on UMCU intraoperative ECoG recordings 11 and then applied to the USZ intraoperative ECoG data 9 , 10 . The SW-SNN detector was then applied to the same dataset for the patients whose resection was guided by hd-ECoG 15 , 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to their event-based processing, spiking neural networks (SNN) are particularly well-suited for bio-signal analysis. Recent work has been done in the detection of HFO with SNN in intracranial EEG 14 , ECoG 15 , 16 , and scalp EEG 17 . In particular, HFO detection in the presurgical intracranial EEG 14 has been performed using ultra-low-power mixed-signal neuromorphic hardware (DYNAP-SE) 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches, drawing from intracranial human and animal data, will, however first have to be adapted and validated on scalp EEG. Furthermore, dedicated HFO detection devices 46 may facilitate future long‐term scalp HFO monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from innovative approaches to optimize the recording of HFOs, various groups focused on the development of more comprehensive detection algorithms as well as the use of new recording technologies using high-resolution cortical arrays with large coverage. In contrast to traditional detectors based on time frequency or signal amplitude features alone [32], the latest HFO detector generation is focusing on not only HFO detection but also on de-noising true HFO detections from artifacts as well as real-time HFO detection, something that is pertinent in intraoperative settings [33,34 ▪ ,35]. The benefit of such systems was shown in a recent work that demonstrated that a deep learning-based classification was able to distill pathological HFOs, regardless of the initial HFO detection methods; this is promising, as it might aid to increase specificity of HFOs for localization of the epileptogenic zone [36].…”
Section: High-frequency Oscillations In Intracranial Electroencephalo...mentioning
confidence: 99%